IMPLEMENTATION OF HIGH LEVEL THINKING SKILLS IN LEARNING - Sri Murwantini (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2022)
This study presents views on the implementation of HOTS in learning to broaden perspectives on HOTS. HOTS includes the ability to transfer, problem solving, and critical thinking or the ability to think creatively and think critically. HOTS implementation is carried out in the planning, implementation, and assessment of learning. HOTS is taught implicitly and explicitly, through activities that are flexible and responsive to the learner, activities that are challenging and fun, and activities that help students gain insight.